Peculiarities of the examination of citrus fruits (mandarins) during the forensic examination - M. V. Harbuz; L. Yu. Ulybina (Bulletin of Kharkiv National University of Internal Affairs)
In today’s environment, the issue of ensuring the identification and safety of imported products is of particular relevance, which is aimed at the successful functioning of the state in the global economy and the reduction of technical barriers to trade. The article discusses the peculiarities of conducting an examination of citrus fruits, in particular, tangerines, with a view to their further classification in the Ukrainian Classifier of Goods for Foreign Economic Activity.